Correlation between Allergic Rhinitis and Laryngopharyngeal Reflux - Alharethy, Sami (Biomed Res Int, 2018)
BACKGROUND AND OBJECTIVES: Laryngopharyngeal reflux (LPR) exhibits nonspecific clinical presentations, and these symptoms may be associated with other conditions such as allergies, including allergic rhinitis and laryngitis. However, there is a gap in the literature regarding the correlation of laryngopharyngeal reflux with allergic rhinitis/laryngitis. Hence, the aim of this study is to explore the correlation between these two conditions. PATIENTS AND METHODS: A total of 126 patients with suggestive manifestations of laryngopharyngeal reflux were included in this study. Patients were classified into LPR positive and negative groups based on the results of a 24-hour oropharyngeal pH monitoring system while allergic rhinitis status was assessed with the score for allergic rhinitis (SFAR). THE RESULTS OF THE TWO GROUPS WERE COMPARED REGARDING THE SFAR SCORE. CORRELATION BETWEEN THE PH RESULTS AND SFAR SCORE WAS EXPLORED. RESULTS: The LPR positive group demonstrated significantly higher SFAR scores compared to the negative LPR group (p < 0.0001). In addition, the Ryan score was significantly correlated with the SFAR total score and its symptomatology-related items (r ranged between 0.35 and 0.5). Conclusion. It seems that laryngopharyngeal reflux increases patients' self-rating of allergic manifestations. It appears that there is an association between laryngopharyngeal reflux and allergic rhinitis/laryngitis.